Isolation and characteristic analysis of a novel strain H7N9 of avian influenza virus A from a patient with influenza-like symptoms in China. (April 2015) - Chen, Faming; Li, Junhua; Sun, Biancheng; Zhang, Hong; Zhang, Rusheng; Yuan, Jie; Ou, Xinhua; Ye, Wen; Chen, Jingfang; Liu, Yunzhi; Huang, Yiwei
Highlights: This study was performed to analyze a new virus strain isolated from a patient infected with influenza A H7N9. Mutations of Q226L and G186 V were found in the hemagglutinin protein (HA) of the new strain. The new strain is more easily able to infect humans. Summary: A novel H7N9 virus (A/Changsha/1/2013(H7N9)) identified through routine examination in the influenza network laboratory was analyzed retrospectively. The gene sequences of A/Changsha/1/2013(H7N9) were highly homologous to other viruses isolated in mainland China. Mutations of Q226L and G186 V were found in the hemagglutinin protein (HA). Amino acid deletions were found at positions 69–73 of the neuraminidase protein (NA) and 218–230 of the non-structural protein (NS1). All viral genes except PB1 were essentially identical to the sequences of other Chinese influenza A H7N9 isolates. Overall, A/Changsha/1/2013(H7N9) is highly homologous to other H7N9 avian influenza viruses isolated in mainland China.